Breaking Through: The Impact of Branding on Early-Stage Brand Success - -, Kezia Tamariska Seraf (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research delves into the urgency and impact of branding strategies on early-stage brands, particularly emphasizing the vital role of effective social media utilization within limited budgets in today’s rapidly digitizing global business landscape. Focused on Bimbelku, an Indonesian accounting and economy platform for students operating for less than a year, the study employs theoretical and experimental methods to analyze how branding strategies through social media contribute to business sustainability. By contrasting the challenges faced by brands lacking a coherent branding strategy with the success observed when guided by strong branding strategies, it highlights the importance of strategic social media use in fostering growth and ensuring longevity through customer engagement. Through this focused case study, practical guidance is offered for early-stage brands, illustrating how to optimize branding strategies and harness digital tools to establish a robust and sustainable presence. This exploration aims to provide a comprehensive understanding of how early-stage brands can navigate the challenges of limited resources while building a strong and lasting brand presence in the digital era. Ultimately, the research aims to equip entrepreneurs with actionable insights, stressing the necessity of adopting robust branding strategies to not only drive profit but also advocate for customer needs in the fiercely competitive digital landscape.